Financial Arbitration: Comparative Perspectives on Islamic and Common Law Approaches - Hassan, Abdiwahid (UIN Sunan Kalijaga Yogyakarta, 2025)
ABSTRACT Research Aims: This paper aims to examine arbitration as a bridge between Islamic finance and international arbitration standards, identifying key areas of convergence and divergence and proposing harmonised solutions that uphold Sharia compliance while ensuring international enforceability. Design/methodology/approach: It evaluates Islamic arbitration frameworks, such as the Accounting and Auditing Organisation for Islamic Financial Institutions (AAOIFI) Sharia Standard on Arbitration and the Asian International Arbitration Centre’s (AIAC, formerly KLRCA) i-Arbitration Rules, against established international benchmarks, including the United Nations Commission on International Trade Law (UNCITRAL) Model Law and the New York Convention. Research Findings: The analysis highlights key areas of convergence and divergence, revealing the complexities of integrating Sharia-compliant dispute resolution within the global legal context. Theoretical Contribution/Originality: The paper proposes practical strategies to harmonise Islamic arbitration practices with international norms, including clarifying and standardising Sharia principles, fostering wider acceptance of Islamic finance arbitration, and ensuring procedural compliance with Sharia and international arbitration frameworks. By doing so, the article argues that arbitration can provide an effective, credible, and globally compatible mechanism to resolve Islamic financial disputes. Research limitations and implications: This study is limited by its focus on comparative legal frameworks, primarily drawing from doctrinal analysis and literature. Review rather than empirical data. Nonetheless, the findings provide practical insights for policymakers, financial institutions, and legal practitioners in designing harmonized arbitration frameworks that align Sharia principles with international commercial standards.